PENGARUH PENGUMUMAN INDONESIA SUSTAINABILITY REPORTING AWARD (ISRA) TERHADAP ABNORMAL RETURN DAN VOLUME PERDAGANGAN SAHAM (STUDI KASUS PADA PERUSAHAAN PERAIH PENGHARGAAN ISRA 2009-2010) - Aldair Rorin Akis; Siti Mutmainah (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2011)
This research studies the impact of Indonesia Sustainability Reporting Award (ISRA) announcementto abnormal return and trading value activity. The impact of award publication could be seenfrom whether there are some differences between abnormal return and trading value activitybefore and after ISRA announcement. The research samples are 16 companies which acceptedthe appreciation of ISRA period 2009-2010. The research data that used is secondary data thatconsist of daily closing price of shares and daily trading volume with an event period 5 days beforeannouncement and 5 days after announcement by used a market adjusted model for expectedreturn. Hypothese are tested by paired samples t-test. The result of this research proves that thereis no difference abnormal return before and after ISRA 2009-2010 announcement, Trading valueactivity have no difference before and after ISRA 2009-2010 announcement.